OECS : making 'small is beautiful' come true. - LEWIS, Vaughan (1994)
Puts into perspective the many challenges which have suddenly emerged to confront the OECS member states. Is of the view that political union may be off the agenda for the time being. Asserts that enhanced domestic harmonisation, together with closer international cooperation, are vital now that the benefits of the protectionist era have ended.